PENURUNAN KADAR AMONIA MENGGUNAKAN KARBON AKTIF DALAM AIR LIMBAH DI PT PURADELTA LESTARI - Nisa Nurhidayanti; Dodit Ardiatma; Ayu Wahyuningtyas; Yuni Hertati (Jurnal Pelita Teknologi, 2019)
Waste water analysis that has been done for PT. Puradelta Lestari has exceeded the ammonia threshold of 25 mg / L. The research objective was to determine the effect of activated carbon by determining the optimum size, optimum time, optimum thickness, and efficiency needed by activated charcoal in reducing ammonia levels of liquid waste. The research method uses a quantitative descriptive approach. The results of the study prove that activated carbon can absorb ammonia in wastewater quite well, from the research that has been done, to determine the optimum condition of activated carbon in absorbing ammonia by varying the mesh size (0.1 mm, 0.25 mm and 0.5 mm) , Media Height (20%, 25%, 30%, 35% and 40%), detention time (10, 15, 20, 25 and 30) minutes in decreasing ammonia, the optimum condition obtained at Mesh size is 0.25mm with Efficiency 78.6%, Media Height at 40% with Efficiency 67.6%, contact time 20 minutes with Efficiency of 78.6%.